3D printing: A qualitative assessment of applications, recent trends and the technology's future potential - Laura Bechthold; Veronika Fischer; Andre Hainzlmaier; Daniel Hugenroth; Ljudmila Ivanova; Kristina Kroth; Benedikt Römer; Edyta Sikorska; Vincent Sitzmann (Expertenkommission Forschung und Innovation (EFI), 2015)
Additive manufacturing (AM) or 3D printing is currently one of the most discussed emerging technologies coming to market with a potentially disruptive power. The terms additive manufacturing (AM) and 3D printing describe production processes in which a solid 3D structure is produced layer by layer by the deposition of suitable materials via an additive manufacturing machine. After around 30 years in the making, 3D printing is about to move from being an industrial rapid prototyping technique to becoming a mainstream manufacturing procedure used by industry and consumers alike. However, the question in which area and to which extent this emerging technology will disrupt state of the art practices is far from trivial. The goal of this report on behalf of the Expert Commission of Research and Innovation is threefold: First, to sketch the emerging 3D printing landscape, explore key trends and the technology's potential. Second, to shed light on 3D printing market dynamics and framework conditions both in Germany and in other countries. Third, to translate the findings into recommendations that can serve as a basis for the Expert Commission's policy report.
Keywords: 330